Exploring Riparian Vegetation Dynamics in East Java: A Focus on the Central Welang Watershed - Putri, Anggraini Aurina; Rahmania, Farhani Nurshafa; Cahyani, Nadila Wulan; Irawanto, Rony (Journal of Earth and Marine Technology (JEMT), 2023)
Indonesia boasts 74 diverse ecosystems, with the riparian system, found in areas like the Welang watershed in Malang Regency, Pasuruan Regency, and Pasuruan City, standing out. These moisture-adapted vegetative zones act as key transitions between aquatic and terrestrial habitats. Human activities in the central Welang watershed could impact its rich vegetation. This study aimed to catalog plant species in the riparian zones and assess their influence on water quality. Utilizing an explorative quantitative descriptive method, research was conducted at four sites in the central Welang watershed in June 2023, encompassing vegetation inventory and water sampling. Findings revealed 67 individual plants from 29 families, predominantly trees, in the central Welang region. This count exceeds the downstream but is less than the upstream. Water quality met the standards, indicating no pollution. Nonetheless, the potential presence of heavy metals necessitates further studies. Understanding Welang's riparian dynamics provides insights into riverbank ecosystems in Indonesia and possibly Southeast Asia. As these zones bridge aquatic and terrestrial environments, they're pivotal for biodiversity, water management, and settlement planning. This research underlines the need to harmonize human progress with ecological conservation, especially as the global focus intensifies on sustainable practices. The study's outcomes can enhance global discussions on riparian ecosystem preservation.